Immunoexpression of human telomerase reverse transcriptase in fibroepithelial tumors of the breast - Fairuz Fairuz; Humaryanto Humaryanto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Phyllodes tumors and fibroadenomas are groups of fibroepithelial tumors in the breast that have different therapeutic approaches due to their rate of progression. The observed phenomenon can be attributed to the proclivity for recurrence and shared histologic characteristics, particularly within the fibroadenoma (FAs), benign phyllodes and borderline phyllodes. It's pathomechanism is undetermined yet. Human telomerase reverse transcriptase (hTERT) is one of the genes thought to play a role in the pathomechanism of this tumor.Objective: This study aimed to determine the comparison of hTERT immunoexpression in the most common fibroepithelial tumor types.Methods: This research was an analytic observational study with cross sectional method. The samples used were FAs and phyllodes tumors (PTs) which were divided according to the 2019 World Health Organization (WHO) classification. Histopathological examination was conducted on paraffin-embedded tissue blocks with FAs and PTs. Staining was performed using immunohistochemistry techniques with hTERT antibodies. Results: A total of 69 samples were obtained consisting of 26 FAs, 17 benign PTs, 16 borderline PTs, and 10 malignant PTs. A significant difference was found in the loss of hTERT expression in fibroadenoma and phyllodes tumors in various grades. There was a positive correlation between hTERT immunoexpression and tumor type in this study (p= 0.0001). Conclusion: There were significant changes in hTERT immunoexpression in fibroepithelial tumors, suggesting a role for hTERT in the pathomechanism of breast fibroepithelial tumors can be considered.